Leadership styles and democratic school - Torres, Leonor Lima (2009)
The Portuguese education system has witnessed, in the last two decades, the emergence of educational policy measures whose reformist agenda has attached growing importance to school management and leadership dimensions. Along this path, marked by trials and morphological adaptations of management bodies, one notes greater acknowledgement of the role leadership plays in the development of school autonomy. Perceived as a politically sound response to the plagues of rising school indiscipline, underachievement and dropout, the leadership theme has been gradually emerging as a fundamental variable in the quest for school excellence, strongly opposed to the historically rooted collegial management culture so widespread in Portuguese schools. Despite the clear the influence of neoliberal thinking in this attempt to reduce school life to the mere expression of indicators of manageralist nature, it is interesting, nevertheless, to study/examine the nature of the relationship between leadership and management styles and school outcomes and the impact this relationship has on the democratic development of the school. In this sense, based on the critical analysis of the external evaluation reports of secondary schools, the central aim of this paper is to discuss the meanings generally attributed to "good leadership", "good school organization and administration" to observe if it is possible to establish some form of link with school outcomes, to understand how the tensions unleashed by this evaluation process influence the organizational settings and practices of different school-objects. One question if this process may not, in fact, represent a "managerialist mission" whose "secret" agenda is to subvert and rewire the logic of autonomous and democratic decision making of schools?